2021
DOI: 10.3352/jeehp.2021.18.3
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of cultural competence education in enhancing knowledge acquisition, performance, attitudes, and student satisfaction among undergraduate health science students: a scoping review

Abstract: Purpose: Cultural competence in healthcare assists in the delivery of culturally sensitive and high-quality services. This scoping review aims to provide an overview of the available evidence and to examine the effectiveness of classroom-based intervention strategies used to enhance the cultural competence of undergraduate health science students.Methods: A comprehensive and systematic literature search was undertaken in databases, including Cochrane Library, Medline, and Emcare. Articles were eligible if they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
3
24
0
2
Order By: Relevance
“…In the first section, the findings indicated that the training program significantly improved cultural competence of the nursing students in the intervention group compared with the control group. Consistent with the results of this study, several studies showed that educational interventions promoted cultural competence among participants (Arruzza & Chau, 2021; Bauer & Bai, 2018; Fair et al, 2021; Lin & Hsu, 2020). In a systematic review, researchers reported that cultural competence training increased the cultural competence of the health care providers.…”
Section: Discussionsupporting
confidence: 92%
“…In the first section, the findings indicated that the training program significantly improved cultural competence of the nursing students in the intervention group compared with the control group. Consistent with the results of this study, several studies showed that educational interventions promoted cultural competence among participants (Arruzza & Chau, 2021; Bauer & Bai, 2018; Fair et al, 2021; Lin & Hsu, 2020). In a systematic review, researchers reported that cultural competence training increased the cultural competence of the health care providers.…”
Section: Discussionsupporting
confidence: 92%
“…Although these training programs can help increase cultural competence, they are insufficient for long-term motivation, attitudes, and behavior change after graduation. Nurse educators and students should pay special attention to cultural competence as a lifetime process, and participation in training programs is required even after years of working in the clinical settings [ 44 ]. Above-mentioned studies may be consistent with the present study because of new and diverse educational content and duration of training.…”
Section: Discussionmentioning
confidence: 99%
“…Through these identities they had differential access to theory and praxis that in turn informed the extent to which they were prepared to engage with issues of diversity per se and intellectual disabilities in particular. Therefore, the development of multi-modal curriculum and co-curricular activities must be leveraged to promote the development of multicultural and diversity competence (Arruzza and Chau, 2021). The discourse on the multidisciplinary team underscored diversity and introduced more intersecting dimensions whereas the discourse on the target group of patients with intellectual disabilities remained undifferentiated (Murray-Garca et al, 2005, 2014).…”
Section: Discussionmentioning
confidence: 99%